Metagenomic Analysis of Soil Bacteria Community Planting Pattern Effect of Rubber-Ganyong Agroforestry System and Rubber Monoculture - Cut Riska Arista; Hidayat Yorianta Sasaerila; Yunus Effendi (EXSACT-A, 2025)
Plantation land with agroforestry is one alternative to reduce the adverse effects of reduced soil fertility quality and loss of microorganism biodiversity. The diversity and abundance of soil microbial communities leads to better nutrient availability in rubber-canna intercroppingg fields than in rubber monoculture lands. Intercroppingg planting patterns containing rhizosphere bacteria beneficial for fertility and availability nutrition and superior phytohormone promoters. Comparison of the presence of bacteria in intercroppingg and monoculture soil soils using metagenomic analysis of 16S rRNA gene sequencing with Bioinformatics method. Analysis of the diversity and abundance of microorganisms using an alpha-diversity matrix of Chao1 and Shannon_E index types. Phylum Proteobacteria were found, which is one of the rhizosphere bacteria whose abundance according to alpha-diversity analysis data reached 49% in intercroppingg and 27% in monoculture fields. Some bacteria of the phylum proteobacteria are: Azospirillum sp., B. zhanjiangense, Phenylobacterium Pseudolabrys sp.  it is reported to play a role in the cycle of improving the quality of soil fertility. In the rubber-canna intercroppingg system, the abundance and microbial communities available on the intercroppingg land are higher in abundance and have specific functions compared to monoculture systems. Therefore the abundance of rhizosphere bacteria produces a more maximal mechanism.